Impairment in T-maze reinforced alternation performance following nucleus basalis magnocellularis lesions in rats. - Salamone, J; Beart, P; Alpert, J; Iversen, S (1984)
Rats were trained on a reinforced alternation paradigm using an elevated T-maze. After pre-surgical training subjects received either ibotenic acid (4 micrograms/0.4 microliter) or vehicle (pH 7.4, 0.4 microliter) bilaterally into the region of the nucleus basalis magnocellularis--an important source of neocortical acetylcholine projections. Acetylcholinesterase staining of sectioned brains revealed a loss of neocortical, but not hippocampal staining in lesioned animals. On the T-maze task, lesioned rats showed significantly impaired choice performance relative to controls. They also demonstrated significant side biases, the degree of which was correlated with choice performance deficit.